The Influence Of Agility, Cyberloafing Behavior, And Empowerment On Organizational Commitment With Work Stress As A Moderating Variable Among Employees In South Jakarta - Annisa Kharenina Augustine; Iwan Kresna Setiadi; Yudi Nur Supriadi (Dinasti Publisher, 2024)
This study aims to analyze the influence of agility, cyberloafing behavior, and empowerment on organizational commitment, with work stress as a moderating variable among employees working in South Jakarta. A survey method was employed, distributing questionnaires to a number of employees selected through purposive sampling. The collected data was then analyzed using Structural Equation Modeling Partial Least Square (SEM PLS) method. The research findings indicate that: (1) agility does not show a significant effect on organizational commitment; (2) cyberloafing behavior has a significant influence on organizational commitment; (3) empowerment also demonstrates a significant effect on organizational commitment; (4) work stress does not moderate the relationship between agility and organizational commitment; (5) work stress does not moderate the relationship between cyberloafing behavior and organizational commitment; and (6) work stress does not moderate the relationship between empowerment and organizational commitment .